Reproductive mortality. - Beral, V (1979)
The transfer from traditional to modern methods of contraception in recent decades has been accompanied by a transfer of deaths from complications of pregnancy to deaths from complications of the modern contraceptive methods. In 1975, for example, it is estimated that there were more deaths at ages 25-44 years in England and Wales from adverse effects of oral contraceptive use than from all complications of pregnancy, delivery, and the puerperium combined. Thus maternal mortality is no longer an adequate indicator of the deaths associated with reproduction in the community. An alternative measure, the reproductive mortality rate should be used, which includes deaths from complications of contraceptive use as well as those from complications of pregnancy or abortion. The reproductive mortality rate in England and Wales seems to have declined continuously since 1950 for women aged 25-34. But after 1960 it increased for women aged 35-44, because of the higher mortality associated with oral contraceptive use in this age group.